Facing the fear: a scaffolding approach to teaching life sciences undergraduates R coding - Paci, Elena; Swainson, Alex; Cerminara, Nadia L. (Frontiers in Education, 2025)
Coding proficiency is becoming an essential skill for future life sciences graduates. Not only must researchers be able to handle and scrutinise increasingly large datasets, but alternative career paths often list coding as a desirable skill for applicants. With the additional advantage of promoting the development of key skills such as problem solving, critical thinking, and group work, there is an increasing need to expose students to principles of coding in a structured and paced way. Despite this, computational tools are often missing from Life Sciences undergraduate curricula. We suggest the reasons for this are barriers faced by both students and staff, which coalesce into a general fear surrounding the topic. From reservations surrounding the complexity of the topic and time input required, to the increased staffing load, there are several factors which contribute to a lack of coding proficiency in Life Sciences curricula. To overcome these barriers, we propose a scaffolding approach using RStudio for data analysis, that has been successfully implemented to teach basic coding skills to students in their first and second years of Neuroscience and Physiology programmes at University of Bristol (UK). We believe that this approach has been a successful route to lower students’ anxiety around coding and ease them into more complex tasks. In this perspective we will reflect on the current barriers, discuss our experience with overcoming them and consider implementations for future iterations.